Molecular docking study of sea urchin (Arbacia lixula) peptides as multi-target inhibitor for non-small cell lung cancer (NSCLC) associated proteins. - Muhammad Hermawan Widyananda; Setyaki Kevin Pratama; Rizky Senna Samoedra; Fikriya Novita Sari; Viol Dhea Kharisma; Arif Nur Muhammad Ansori; Yulanda Antonius (Journal of Pharmacy & Pharmacognosy Research, 2021)
Context: Lung cancer is a type of cancer that causes the most deaths worldwide. The most common type of lung cancer is non-small cell lung cancer (NSCLC). Sea urchin (Arbacia lixula) has high potential as an anti-NSCLC agent.